How is managerial remuneration determined in India?. Issue 2 (2nd May 2017) - Kang, Lakhwinder Singh; Nanda, Payal
Abstract : Purpose: The purpose of this paper is to analyse the impact of company performance, governance structure and ownership structure in determining the managerial remuneration for 134 listed companies in India over the years 2003-2012. Design/methodology/approach: Remuneration paid to the board of directors of companies is taken to represent the managerial remuneration. Exogeneity among the company performance measures is verified with the endogtest suggested in Baum et al. (2007). A fixed effects panel regression with clustered standard errors is employed after checking for the presence of heteroskedasticity, autocorrelation and cross-sectional dependence in the data. Findings: The study reveals that managerial remuneration increases as the accounting performance of companies improves, whereas the market performance of companies has no significant association with managerial remuneration. The study also shows that foreign institutional shareholding is significantly and positively related with managerial remuneration in India. Research limitations/implications: This study highlights the various factors which affect the determination of managerial remuneration in India. These findings can be used as inputs by regulatory authorities in framing and improving governance norms regarding managerial remuneration. This study also suggests that factors other than the number, the independence and objectivity of independent directors are more important in determining managerial remuneration. Originality/value: The present study proposes more reliable results, obtained through a fixed effects panel regression model with clustered standard error estimates and also checks endogeneity of performance measures with the endogtest, which is the appropriate test to use for verifying endogeneity in panel data.